Analisis Flypaper Effect Belanja Daerah Kabupaten/Kota di Sulawesi - Armawaddin, Muhamad; Rumbia, Wali Aya; Afiat, Muhammad Nur (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
This study aims to determine the phenomenon of flypaper effect of regionally spending in Sulawesi. Types of data use secondary data about regionally original income, general allocation fund, special allocation fund, tax-sharing fund, and regionally spending in 2016–2017. Data analysis using panel data regression analysis. Result of research, found flypaper effect of regional spending from special allocation fund, whereas from general allocation fund and tax-sharing fund is not found. This study also proves that regionally spending, general allocation fund, special allocation fund, and tax-sharing fund have a significant influence on regionally spending in Sulawesi.